Getting better - Tanner, Gill; Wood, Tim Murray, Maggie Tourret, Pat (A & C Black London, 1994)
Each of the books in this series explores a different theme, using colour photographs of "mystery" objects from the 1900s, the 1930s and the 1960s. The reader is encouraged to look for clues and to guess what the object is. This book looks at how being ill has changed since the 1900s.